2008
DOI: 10.1002/hep.22751
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus suppresses toll-like receptor-mediated innate immune responses in murine parenchymal and nonparenchymal liver cells

Abstract: We have previously shown that Toll-like receptor (TLR)-activated murine nonparenchymal liver cells [(NPC); Kupffer cells (KC), liver sinusoidal endothelial cells (LSEC)]T he hepatitis B virus (HBV) is a hepatotropic DNA virus that can lead to chronic hepatitis, which can be complicated by the development of liver cirrhosis and hepatocellular carcinoma. Current approved therapeutic strategies for treatment HBV include interferon-alpha (IFN-␣) and nucleoside and nucleotide analogs. 1,2 However, only a minority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
239
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(254 citation statements)
references
References 147 publications
(209 reference statements)
9
239
0
1
Order By: Relevance
“…Previous studies demonstrate that HBV has evolved mechanisms to overcome TLR-mediated IFN signaling. 30 In accordance with these previous studies, the identification of an inhibitory role for HBx in virustriggered IFN signaling helps to explain how HBV evades the PRRmediated innate immune response, which results in viral evasion of the immune system and chronic infection of the host.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies demonstrate that HBV has evolved mechanisms to overcome TLR-mediated IFN signaling. 30 In accordance with these previous studies, the identification of an inhibitory role for HBx in virustriggered IFN signaling helps to explain how HBV evades the PRRmediated innate immune response, which results in viral evasion of the immune system and chronic infection of the host.…”
Section: Discussionsupporting
confidence: 70%
“…29 The Wu group also determined that Toll-like receptors mediate IRF3 and IFN-b activation and can be inhibited by a high level of HBV replication in HBV-Met cells. 30 These results suggest that HBV has evolved mechanisms to overcome the innate immune response of the host cell.…”
Section: Introductionmentioning
confidence: 97%
“…HBsAg, HBeAg and HBV virions may also inhibit the activation of liver NPCs by TLR3 ligands. 32 Coculture of hepatic NPC cell supernatants containing HBsAg, HBeAg and HBV virions resulted in abrogation of TLR-induced antiviral activity, correlating with decreased activation of IRF-3, NF-kB and ERK1/2 in NPCs. Our recent data suggested that HBsAg may trigger IL-10 production in hepatic cells and thereby, attenuate the TLR3-mediated activation of NPCs.…”
Section: Interaction Between Tlrs and Hbvmentioning
confidence: 93%
“…In mice, hepatitis B surface antigens (HBsAg), hepatitis envelope antigen (HBeAg), and HBV virions are capable of inhibiting TLR-dependent pathways [25]. HBV-X protein directly degrades adaptor molecule MAVS, resulting in the inhibition of RIG-I-dependent signaling pathways [26].…”
Section: Pattern Recognition Receptors In Hbv Infectionmentioning
confidence: 99%